Application of G-quadruplex aptamer conjugated MSNs to deliver ampicillin for suppressing S. aureus biofilm on mice bone - Mohammad Moradi; Hassan Mohabatkar; Mandana Behbahani; Ghasem Dini (Arabian Journal of Chemistry, 2022)
Staphylococcus aureus is a common bacterial agent of biofilm formation in medical environments. The formed biofilm of this bacterium in bone tissue is one of the main causes of osteomyelitis, which is a serious health issue. Due to the importance of this infection after traumatic injuries or surgical intervention, it is necessary to develop a system that could release the antibiotics at the site of injury, specifically and gradually. The current study aimed to develop a nanosystem composed of single-stranded G-quadreplex DNA aptamer as the bio-recognition element, mesoporous silica nanoparticles (MSNs) as the carrier for gradual drug release, and Ampicillin as the cargo to be delivered to the site of infection. In silico methods were used to select an optimum binding aptamer against protein A of S. aureus. The binding of aptamer was confirmed via gel retardation assay, DLS, and Zeta potential analyses. The loading of the drug was confirmed by the FTIR method, and the drug release investigation showed almost 30 % of drug release via 48 h dialysis assay. The acquired results from the biofilm suppression assay indicated that this system provides a significant inhibitory effect against the S. aureus biofilm and has a high potential for the desired drug release to prevent the formation of biofilm, and could destroy the biofilm on the mice bone. The results of the MTT assay proved that this system does not pose a significant toxicity thread for MCF-7 cell viability, as a model for eukaryotic cells. In vivo studies are required to further confirm the efficacy of this system against S. aureus biofilm on bone.